Validasi Metode X-Ray Fluorescence untuk Analisis Ion Fe dalam activated Methyl Diethanol Amine (aMDEA) - Panggabean, Aman S.; Rachman, Arief (Indonesian Journal of Chemical Research, 2016)
A research about validation method of Fe analysis in activated Methyl Diethanol Amine (aMDEA) using X-Ray Fluurescence (XRF) has been done. Analysis of Fe ion in aMDEA was performed to find out the rising of Fe in aMDEA that will show corrosion or metal erosion is caused by aMDEA degradation and contamination or accumulation from heat stable salt that can dissolve or scrape the film coat in carbon steel. Validation is done consist of linearity, accuracy, precision, limit of detection, and limit of quantitation. The analytical performance of the XRF for determination of Fe ions is good, shown as coefficient of correlation are 0.9997, repeatability as % RSD value are 1,93 % less than 2/3 CV Horwitz 6.24 %, percentage of recovery are 103.35 % . The LOD and LOQ are 0.351 and 2.975 ppm respectively, and Fe selectivity in aMDEA at 6.4 keV. The results obtained showed the XRF can be used for the routine analysis in the determination of Fe ions aMDEA samples.